Adhesive for composite glass fiber cloth copper clad plate and preparation method thereof
Through the combination of modified graphene oxide and flame retardant curing agent, the bonding, corrosion resistance and flame retardant properties of epoxy resin adhesives are improved, and the problem of insufficient performance of existing epoxy resin adhesives in copper clad applications is solved, satisfying the problem of insufficient performance of existing epoxy resin adhesives. The composite material needs of high-performance copper clad plates.
Patent Information
- Application Number
- CN202411393302.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-08
AI Technical Summary
Existing epoxy resin adhesives have problems in insufficient bonding performance, corrosion resistance and flame retardant properties in copper clad applications, which is difficult to meet the needs of high-performance copper clad for conduction, insulation and support.
Adhesive for glass fiber cloth copper-clad plate composite with modified graphene oxide, flame retardant curing agent and γ-aminopropyltrimethoxysilane, are modified by aminating graphene oxide, metal hydroxide deposition and silane. , form a maze effect and chemical bonding to improve bonding performance; use organosilane chains and phosphorus structures to enhance flame retardant performance.
It significantly improves the adhesive strength, corrosion resistance and flame retardant properties, and meets the application needs of high-performance copper clad plates.
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesives, in particular to an adhesive for composite glass fiber cloth copper clad plates and a preparation method thereof. Background Art
[0002] Copper clad laminate is a plate-like material made by impregnating reinforcing materials with resin, covering one or both sides with copper foil, and hot pressing. It is the base material for preparing printed circuit boards. Printed circuit boards of various forms and functions are made by selectively processing, etching, drilling and copper plating on copper clad laminates to make different printed circuits. Copper clad laminates mainly play the role of interconnection, insulation and support for printed circuit boards, and have a great influence on the transmission speed, energy loss and characteristic impedance of signals in the circuit. With the development of electronic and electrical equipment towards light, thin, short, multifunctional and intelligent directions and the continuous advancement of electronic packaging technology, high-density interconnected printed circuit board products with technical characteristics of miniaturized vias, refined wires and thin dielectric layers have rapidly emerged, and the demand for high-performance copper clad laminates is increasing.
[0003] Epoxy resin has a small curing shrinkage rate, and its cured product has excellent adhesion, heat resistance, chemical resistance, mechanical properties, and electrical properties. Therefore, it has been widely used in various fields of the national economy, such as electronics, machinery manufacturing, aerospace, light industry, and daily life. As a commonly used adhesive for copper clad laminates, epoxy resin adhesives have increasingly higher requirements for their performance, so epoxy resin adhesives with excellent performance have great market advantages. Summary of the invention
[0004] The object of the present invention is to provide an adhesive for glass fiber cloth copper clad laminate composite and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A glass fiber cloth copper clad laminate composite adhesive, characterized in that, by weight, it mainly comprises 8 to 12 parts of modified graphene oxide, 90 to 110 parts of epoxy resin, 55 to 65 parts of flame retardant curing agent, and 15 to 25 parts of γ-aminopropyltrimethoxysilane.
[0007] As an optimization, the modified graphene oxide is prepared by amination of graphene oxide with ethylenediamine, deposition of metal hydroxide, and modification with hexadecyltrimethoxysilane.
[0008] As an optimization, the flame retardant curing agent is prepared by hydrolysis of DOPO-based trimethoxysilane, γ-aminopropyl dimethoxymethylsilane, and dimethyldimethoxysilane.
[0009] A method for preparing an adhesive for glass fiber cloth copper clad laminate composite, comprising the following preparation steps:
[0010] (1) Mix aminated graphene oxide and deionized water in a mass ratio of 1: (400-600) and ultrasonicate for 2-3 h to obtain a suspension; mix zinc nitrate hexahydrate, aluminum nitrate nonahydrate, urea, and deionized water in a mass ratio of (2-2.2): (1-1.2): (8.5-8.7): (25-35) and drip into the suspension at a rate of 3-5 g / min. Stop dripping when the pH value is 8.5-9.0 and stir at a speed of 60-80 r / min at room temperature. Stir for 0.5-1.5h, wash the solid product with deionized water and centrifuge until the pH value of the washing solution is 7.0, freeze-dry the solid product for 22-26h, immerse in a 10% volume concentration of hexadecyltrimethoxysilane ethanol solution, ultrasonicate for 25-35min, stir at 200-300r / min at room temperature for 0.5-1.5h, filter, wash the filter residue with deionized water for 3-5 times, freeze-dry for 22-26h, and obtain modified graphene oxide;
[0011] (2) γ-aminopropyldimethoxymethylsilane, DOPO-trimethoxysilane and dimethyldimethoxysilane were mixed in a molar ratio of 1:1:1, methyl ethyl ketone (2-4 times the mass of DOPO-trimethoxysilane) and anhydrous methanol (1-3 times the mass of DOPO-trimethoxysilane) were added, and 1 mol / L sodium hydroxide solution (0.02-0.04 times the mass of DOPO-trimethoxysilane) was added dropwise at 20-30 drops / min at 0°C. The reaction was continued at 0°C for 0.5-1.5 h, and the temperature was raised to 70-80°C and the reaction was continued for 25-35 h. Dichloromethane (equal volume of methyl ethyl ketone) and deionized water (equal volume of methyl ethyl ketone) were added and stirred, and the mixture was allowed to stand for stratification. The organic phase was taken and the operation was repeated 3-5 times. The organic phase was dried under reduced pressure at 40-45°C and 40-60 kPa for 4-6 h to obtain a flame retardant curing agent.
[0012] (3) The modified graphene oxide and epoxy resin are stirred at a mass ratio of 1:(9-11) at 170-190°C at a rate of 60-80 r / min for 0.5-1.5 h, and a flame retardant curing agent (0.5-0.7 times the mass of the epoxy resin) and γ-aminopropyltrimethoxysilane (0.1-0.3 times the mass of the epoxy resin) are added. The stirring is continued for 10-20 min, and vacuum degassing is performed for 10-20 min to obtain an adhesive for glass fiber cloth copper clad laminate composite.
[0013] As an optimization, the graphene oxide is industrial-grade graphene oxide, which is purchased from Suzhou Carbonfeng Graphite Technology Co., Ltd.; the aminated graphene oxide is prepared by mixing graphene oxide and deionized water in a mass ratio of 1: (190~210), ultrasonicating for 25~35 minutes to obtain a graphene oxide suspension, mixing the graphene oxide suspension and ethylenediamine in a mass ratio of 1: (7~8), stirring at 65~75°C and a speed of 60~80r / min for 1.5~2.5 hours, centrifuging to obtain a solid product, washing it with deionized water for 3~5 times, and freeze-drying it for 46~50 hours.
[0014] As an optimization, the DOPO-based trimethoxysilane in step (2) is prepared by mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and dimethoxymethylvinylsilane in a molar ratio of 1:1, adding chloroform in an amount of 0.7 to 0.9 times the mass of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, stirring at 60 to 80 r / min for 3.5 to 4.5 h at 65 to 75 ° C, adding azobisisobutyronitrile in an amount of 0.01 to 0.03 times the molar number of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to the above system in three times, stirring at 65 to 75 ° C at a rate of 60 to 80 r / min for 9 to 11 h, cooling to room temperature, and rotary evaporating at 35 to 45 ° C for 2 to 3 h.
[0015] As an optimization, the epoxy resin in step (3) is E-51 epoxy resin.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0017] When preparing the adhesive for composite glass fiber cloth copper clad plate, the present invention comprises the following steps: subjecting graphene oxide to ethylenediamine amination, metal hydroxide deposition and hexadecyltrimethoxysilane modification to obtain modified graphene oxide; hydrolyzing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide-based trimethoxysilane, γ-aminopropyldimethoxymethylsilane and dimethyldimethoxysilane to obtain a flame retardant curing agent; and evenly mixing epoxy resin, modified graphene oxide, the flame retardant curing agent and γ-aminopropyltrimethoxysilane and performing vacuum degassing to obtain the adhesive for composite glass fiber cloth copper clad plate.
[0018] First, the amine groups on the surface of graphene oxide after amination have a strong adsorption effect on metal cations, so that zinc ions and aluminum ions are tightly adsorbed on the surface of graphene oxide, which is beneficial to the formation of layered double hydroxide layers, improves the dispersibility of graphene oxide, and helps the layered structure of graphene oxide to disperse in the adhesive to form a maze effect, prolongs the diffusion path of oxygen and water molecules to the metal surface, and improves the corrosion resistance of the adhesive; the surface of modified graphene oxide modified by hexadecyltrimethoxysilane has long-chain alkyl groups, which makes it hydrophobic and further improves the corrosion resistance; γ-aminopropyltrimethoxysilane contains rich silicon-oxygen bonds, which can form chemical bonds with the surface of the copper clad laminate, thereby improving the bonding performance of the adhesive.
[0019] Secondly, the flame retardant curing agent is formed by the hydrolysis of γ-aminopropyldimethoxymethylsilane, DOPO-based trimethoxysilane, and dimethyldimethoxysilane methoxy groups to form an organic silane chain. On the one hand, phosphorus is introduced into the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide on the molecular chain to give the adhesive a flame retardant effect, and synergistically flame retardant with the organic silicon on the chain segment, so that the adhesive has good flame retardant properties. On the other hand, the flexible organic silane chain can effectively improve the toughness of the adhesive and improve its mechanical properties. The double metal hydroxide layer deposited on the surface of the modified graphene oxide will release water and carbon dioxide when heated, which can dilute the combustible gas. The double metal hydroxide can also act as a physical barrier to isolate flames and absorb smoke particles, thereby effectively improving the flame retardant properties of the adhesive. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] Example 1
[0022] A method for preparing an adhesive for glass fiber cloth copper clad laminate composite, comprising the following preparation steps:
[0023] (1) The aminated graphene oxide and deionized water were mixed at a mass ratio of 1:400 and ultrasonicated for 2 hours to obtain a suspension; zinc nitrate hexahydrate, aluminum nitrate nonahydrate, urea, and deionized water were mixed at a mass ratio of 2:1:8.5:25, and dripped into the suspension at a rate of 3 g / min. The dripping was stopped when the pH value was 8.5, and the mixture was stirred at a speed of 60-80 r / min for 0.5 h at room temperature. The solid product was washed with deionized water and centrifuged until the pH value of the washing solution was 7.0. The solid product was freeze-dried for 22 hours, immersed in a hexadecyltrimethoxysilane ethanol solution with a volume concentration of 10%, ultrasonicated for 25 minutes, stirred at a speed of 200 r / min for 0.5 h at room temperature, filtered, and the filter residue was washed with deionized water for 3 times, and freeze-dried for 22 hours to obtain modified graphene oxide;
[0024] (2) γ-aminopropyldimethoxymethylsilane, DOPO-trimethoxysilane and dimethyldimethoxysilane were mixed in a molar ratio of 1:1:1, methyl ethyl ketone (2 times the mass of DOPO-trimethoxysilane) and anhydrous methanol (1 times the mass of DOPO-trimethoxysilane) were added, and a 1 mol / L sodium hydroxide solution (0.02 times the mass of DOPO-trimethoxysilane) was added dropwise at 20 drops / min at 0°C. The reaction was continued at 0°C for 0.5 h, and the temperature was raised to 70°C and the reaction was continued for 25 h. Dichloromethane and deionized water were added in an equal volume of methyl ethyl ketone and methyl ethyl ketone, respectively, and the mixture was stirred evenly. The mixture was allowed to stand for stratification, and the organic phase was taken. The operation was repeated 3 times. The organic phase was dried under reduced pressure at 40°C and 40 kPa for 4 h to obtain a flame retardant curing agent.
[0025] (3) The modified graphene oxide and epoxy resin were stirred at a mass ratio of 1:9 at 170°C at a rate of 60 r / min for 0.5 h, and a flame retardant curing agent (0.5 times the mass of the epoxy resin) and γ-aminopropyltrimethoxysilane (0.1 times the mass of the epoxy resin) were added. The stirring was continued for 10 min, and vacuum degassing was performed for 10 min to obtain an adhesive for glass fiber cloth copper clad laminate composite.
[0026] Example 2
[0027] A method for preparing an adhesive for glass fiber cloth copper clad laminate composite, comprising the following preparation steps:
[0028] (1) The aminated graphene oxide and deionized water were mixed at a mass ratio of 1:500 and ultrasonicated for 2.5 hours to obtain a suspension; zinc nitrate hexahydrate, aluminum nitrate nonahydrate, urea, and deionized water were mixed at a mass ratio of 2.1:1.1:8.6:30, and dripped into the suspension at a rate of 4 g / min. The dripping was stopped when the pH value was 8.7, and the mixture was stirred at a speed of 70 r / min for 1 hour at room temperature. The solid product was washed with deionized water and centrifuged until the pH value of the washing solution was 7.0. The solid product was freeze-dried for 24 hours, immersed in a hexadecyltrimethoxysilane ethanol solution with a volume concentration of 10%, ultrasonicated for 30 minutes, stirred at a speed of 250 r / min for 1 hour at room temperature, filtered, and the filter residue was washed 4 times with deionized water, and freeze-dried for 24 hours to obtain modified graphene oxide;
[0029] (2) γ-aminopropyldimethoxymethylsilane, DOPO-trimethoxysilane and dimethyldimethoxysilane were mixed in a molar ratio of 1:1:1, methyl ethyl ketone (3 times the mass of DOPO-trimethoxysilane) and anhydrous methanol (2 times the mass of DOPO-trimethoxysilane) were added, and a 1 mol / L sodium hydroxide solution (0.03 times the mass of DOPO-trimethoxysilane) was added dropwise at 25 drops / min at 0°C. The reaction was continued at 0°C for 1 hour, and the temperature was raised to 75°C and the reaction was continued for 30 hours. Dichloromethane (an equal volume of methyl ethyl ketone) and deionized water (an equal volume of methyl ethyl ketone) were added and stirred, and the mixture was allowed to stand for stratification. The organic phase was taken and the operation was repeated 4 times. The organic phase was dried under reduced pressure at 42°C and 50 kPa for 5 hours to obtain a flame retardant curing agent.
[0030] (3) The modified graphene oxide and epoxy resin were stirred at a mass ratio of 1:10 at 180°C at a rate of 70 r / min for 1 h, and a flame retardant curing agent (0.6 times the mass of the epoxy resin) and γ-aminopropyltrimethoxysilane (0.2 times the mass of the epoxy resin) were added. The stirring was continued for 15 min, and vacuum degassing was performed for 15 min to obtain an adhesive for glass fiber cloth copper clad laminate composite.
[0031] Example 3
[0032] A method for preparing an adhesive for glass fiber cloth copper clad laminate composite, comprising the following preparation steps:
[0033] (1) The aminated graphene oxide and deionized water were mixed at a mass ratio of 1:600 and ultrasonicated for 3 hours to obtain a suspension; zinc nitrate hexahydrate, aluminum nitrate nonahydrate, urea, and deionized water were mixed at a mass ratio of 2.2:1.2:8.7:35, and dripped into the suspension at a rate of 4 g / min. The dripping was stopped when the pH value was 9.0, and the mixture was stirred at a speed of 80 r / min for 1.5 hours at room temperature. The solid product was washed with deionized water and centrifuged until the pH value of the washing solution was 7.0. The solid product was freeze-dried for 26 hours, immersed in a hexadecyltrimethoxysilane ethanol solution with a volume concentration of 10%, ultrasonicated for 35 minutes, stirred at a speed of 300 r / min for 1.5 hours at room temperature, filtered, and the filter residue was washed with deionized water 5 times, and freeze-dried for 26 hours to obtain modified graphene oxide;
[0034] (2) γ-aminopropyldimethoxymethylsilane, DOPO-trimethoxysilane and dimethyldimethoxysilane were mixed in a molar ratio of 1:1:1, methyl ethyl ketone (4 times the mass of DOPO-trimethoxysilane) and anhydrous methanol (3 times the mass of DOPO-trimethoxysilane) were added, and a 1 mol / L sodium hydroxide solution (0.04 times the mass of DOPO-trimethoxysilane) was added dropwise at 30 drops / min at 0°C. The reaction was continued at 0°C for 1.5 h, and the temperature was raised to 80°C and the reaction was continued for 35 h. An equal volume of dichloromethane and an equal volume of deionized water were added to the mixture, and the mixture was stirred evenly. The mixture was allowed to stand for stratification, and the organic phase was taken. The operation was repeated 5 times. The organic phase was dried under reduced pressure at 45°C and 60 kPa for 6 h to obtain a flame retardant curing agent.
[0035] (3) The modified graphene oxide and epoxy resin were stirred at a mass ratio of 1:11 at 190°C at a rate of 80 r / min for 1.5 h, and a flame retardant curing agent (0.7 times the mass of the epoxy resin) and γ-aminopropyltrimethoxysilane (0.3 times the mass of the epoxy resin) were added. The stirring was continued for 20 min, and vacuum degassing was performed for 20 min to obtain an adhesive for glass fiber cloth copper clad laminate composite.
[0036] Comparative Example 1
[0037] A method for preparing an adhesive for glass fiber cloth copper clad laminate composite, comprising the following preparation steps:
[0038] (1) The aminated graphene oxide and deionized water were mixed at a mass ratio of 1:500 and ultrasonicated for 2.5 hours to obtain a suspension; zinc nitrate hexahydrate, aluminum nitrate nonahydrate, urea, and deionized water were mixed at a mass ratio of 2.1:1.1:8.6:30, and dripped into the suspension at a rate of 4 g / min. The dripping was stopped when the pH value was 8.7, and the mixture was stirred at a speed of 70 r / min for 1 hour at room temperature. The solid product was washed with deionized water and centrifuged until the pH value of the washing solution was 7.0. The solid product was freeze-dried for 24 hours to obtain modified graphene oxide;
[0039] (2) γ-aminopropyldimethoxymethylsilane, DOPO-trimethoxysilane and dimethyldimethoxysilane were mixed in a molar ratio of 1:1:1, methyl ethyl ketone (3 times the mass of DOPO-trimethoxysilane) and anhydrous methanol (2 times the mass of DOPO-trimethoxysilane) were added, and a 1 mol / L sodium hydroxide solution (0.03 times the mass of DOPO-trimethoxysilane) was added dropwise at 25 drops / min at 0°C. The reaction was continued at 0°C for 1 hour, and the temperature was raised to 75°C and the reaction was continued for 30 hours. Dichloromethane (an equal volume of methyl ethyl ketone) and deionized water (an equal volume of methyl ethyl ketone) were added and stirred, and the mixture was allowed to stand for stratification. The organic phase was taken and the operation was repeated 4 times. The organic phase was dried under reduced pressure at 42°C and 50 kPa for 5 hours to obtain a flame retardant curing agent.
[0040] (3) The modified graphene oxide and epoxy resin were stirred at a mass ratio of 1:10 at 180°C at a rate of 70 r / min for 1 h, and a flame retardant curing agent (0.6 times the mass of the epoxy resin) and γ-aminopropyltrimethoxysilane (0.2 times the mass of the epoxy resin) were added. The stirring was continued for 15 min, and vacuum degassing was performed for 15 min to obtain an adhesive for glass fiber cloth copper clad laminate composite.
[0041] Comparative Example 2
[0042] A method for preparing an adhesive for glass fiber cloth copper clad laminate composite, comprising the following preparation steps:
[0043] (1) immersing graphene oxide in a 10% volume concentration hexadecyltrimethoxysilane ethanol solution, ultrasonicating for 30 min, stirring at 250 r / min at room temperature for 1 h, filtering, washing the filter residue with deionized water for 4 times, and freeze-drying for 24 h to obtain modified graphene oxide;
[0044] (2) γ-aminopropyldimethoxymethylsilane, DOPO-trimethoxysilane and dimethyldimethoxysilane were mixed in a molar ratio of 1:1:1, methyl ethyl ketone (3 times the mass of DOPO-trimethoxysilane) and anhydrous methanol (2 times the mass of DOPO-trimethoxysilane) were added, and a 1 mol / L sodium hydroxide solution (0.03 times the mass of DOPO-trimethoxysilane) was added dropwise at 25 drops / min at 0°C. The reaction was continued at 0°C for 1 hour, and the temperature was raised to 75°C and the reaction was continued for 30 hours. Dichloromethane (an equal volume of methyl ethyl ketone) and deionized water (an equal volume of methyl ethyl ketone) were added and stirred, and the mixture was allowed to stand for stratification. The organic phase was taken and the operation was repeated 4 times. The organic phase was dried under reduced pressure at 42°C and 50 kPa for 5 hours to obtain a flame retardant curing agent.
[0045] (3) The modified graphene oxide and epoxy resin were stirred at a mass ratio of 1:10 at 180°C at a rate of 70 r / min for 1 h, and a flame retardant curing agent (0.6 times the mass of the epoxy resin) and γ-aminopropyltrimethoxysilane (0.2 times the mass of the epoxy resin) were added. The stirring was continued for 15 min, and vacuum degassing was performed for 15 min to obtain an adhesive for glass fiber cloth copper clad laminate composite.
[0046] Comparative Example 3
[0047] A method for preparing an adhesive for glass fiber cloth copper clad laminate composite, comprising the following preparation steps:
[0048] (1) The aminated graphene oxide and deionized water were mixed at a mass ratio of 1:500 and ultrasonicated for 2.5 hours to obtain a suspension; zinc nitrate hexahydrate, aluminum nitrate nonahydrate, urea, and deionized water were mixed at a mass ratio of 2.1:1.1:8.6:30, and dripped into the suspension at a rate of 4 g / min. The dripping was stopped when the pH value was 8.7, and the mixture was stirred at a speed of 70 r / min for 1 hour at room temperature. The solid product was washed with deionized water and centrifuged until the pH value of the washing solution was 7.0. The solid product was freeze-dried for 24 hours, immersed in a hexadecyltrimethoxysilane ethanol solution with a volume concentration of 10%, ultrasonicated for 30 minutes, stirred at a speed of 250 r / min for 1 hour at room temperature, filtered, and the filter residue was washed 4 times with deionized water, and freeze-dried for 24 hours to obtain modified graphene oxide;
[0049] (2) The modified graphene oxide and epoxy resin were stirred at a mass ratio of 1:10 at 180°C at a rate of 70 r / min for 1 h, and linear phenolic resin (0.6 times the mass of epoxy resin) and γ-aminopropyltrimethoxysilane (0.2 times the mass of epoxy resin) were added. The stirring was continued for 15 min, and vacuum degassing was performed for 15 min to obtain an adhesive for glass fiber cloth copper clad laminate composite.
[0050] Comparative Example 4
[0051] A method for preparing an adhesive for glass fiber cloth copper clad laminate composite, comprising the following preparation steps:
[0052] (1) The aminated graphene oxide and deionized water were mixed at a mass ratio of 1:500 and ultrasonicated for 2.5 hours to obtain a suspension; zinc nitrate hexahydrate, aluminum nitrate nonahydrate, urea, and deionized water were mixed at a mass ratio of 2.1:1.1:8.6:30, and dripped into the suspension at a rate of 4 g / min. The dripping was stopped when the pH value was 8.7, and the mixture was stirred at a speed of 70 r / min for 1 hour at room temperature. The solid product was washed with deionized water and centrifuged until the pH value of the washing solution was 7.0. The solid product was freeze-dried for 24 hours, immersed in a hexadecyltrimethoxysilane ethanol solution with a volume concentration of 10%, ultrasonicated for 30 minutes, stirred at a speed of 250 r / min for 1 hour at room temperature, filtered, and the filter residue was washed 4 times with deionized water, and freeze-dried for 24 hours to obtain modified graphene oxide;
[0053] (2) γ-aminopropyldimethoxymethylsilane, DOPO-trimethoxysilane and dimethyldimethoxysilane were mixed in a molar ratio of 1:1:1, methyl ethyl ketone (3 times the mass of DOPO-trimethoxysilane) and anhydrous methanol (2 times the mass of DOPO-trimethoxysilane) were added, and a 1 mol / L sodium hydroxide solution (0.03 times the mass of DOPO-trimethoxysilane) was added dropwise at 25 drops / min at 0°C. The reaction was continued at 0°C for 1 hour, and the temperature was raised to 75°C and the reaction was continued for 30 hours. Dichloromethane (an equal volume of methyl ethyl ketone) and deionized water (an equal volume of methyl ethyl ketone) were added and stirred, and the mixture was allowed to stand for stratification. The organic phase was taken and the operation was repeated 4 times. The organic phase was dried under reduced pressure at 42°C and 50 kPa for 5 hours to obtain a flame retardant curing agent.
[0054] (3) The modified graphene oxide and epoxy resin were stirred at a mass ratio of 1:10 at 180°C at a rate of 70 r / min for 1 h, and a flame retardant curing agent (0.6 times the mass of the epoxy resin) was added. The stirring was continued for 15 min, and vacuum degassing was performed for 15 min to obtain an adhesive for glass fiber cloth copper clad laminate composite.
[0055] Test Example 1
[0056] Bond strength test:
[0057] Test method: Use the ASIDA-NW11C peel strength tester of Zhengye Electronics, take a sample with a specification of 10mm×130mm for testing, peel off the glass fiber cloth on one edge of the sample from the copper clad board by about 12mm, then fix the sample on the sample holder, and clamp the peeled glass fiber cloth with the sample clamp so that the glass fiber cloth is perpendicular to the copper clad board, turn on the peeling machine, and apply pressure evenly, so that the force direction is always perpendicular to the direction of the substrate material. Determine the value when the peel length is greater than 25mm, and calculate the minimum load required per unit width, which is the peel strength, in N / mm. The results are shown in Table 1.
[0058] Table 1
[0059] Peel strength (N / mm) Peel strength (N / mm) Example 1 1.6 Comparative Example 1 1.4 Example 2 1.7 Comparative Example 2 1.6 Example 3 1.4 Comparative Example 3 1.5 Comparative Example 4 1.2
[0060] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the adhesive for composite glass fiber cloth copper clad laminate prepared by the present invention has good bonding strength.
[0061] By comparison, the peel strength of Examples 1 to 3 is greater than the peel strength of Comparative Example 4, indicating that γ-aminopropyltrimethoxysilane contains abundant silicon-oxygen bonds and can form chemical bonds with the surface of the copper clad laminate, thereby improving the bonding performance of the adhesive.
[0062] Flame retardant performance test:
[0063] Test method: The examples and comparative examples were prepared into standard specimens according to GB / T 2406.2, and the limiting oxygen index of the standard specimens was tested. The results are shown in Table 2.
[0064] Table 2
[0065] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 37.6 Comparative Example 1 36.8 Example 2 38.1 Comparative Example 2 30.6 Example 3 37.9 Comparative Example 3 23.1 Comparative Example 4 33.5
[0066] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 2 and 3 in Table 2, it can be found that the adhesive for composite glass fiber cloth copper clad laminate prepared by the present invention has good flame retardant properties.
[0067] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that the double metal hydroxide layer deposited on the surface of the modified graphene oxide releases water and carbon dioxide when heated, which can dilute the combustible gas, and the double metal hydroxide can also act as a physical barrier to isolate flames and absorb smoke particles, thereby effectively improving the flame retardant properties of the adhesive; the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that phosphorus and silicon are introduced into the organic silane chain formed by the hydrolysis of methoxy groups of γ-aminopropyldimethoxymethylsilane, DOPO-based trimethoxysilane, and dimethyldimethoxysilane, giving the adhesive a good flame retardant effect.
[0068] Test Example 3
[0069] Corrosion resistance test:
[0070] Test method: Use Q-Fog salt spray box to conduct neutral salt spray test, the solution concentration is 5% sodium chloride solution. The experimental temperature is 35℃±2℃. The sample is placed at a 45° angle to the horizontal plane. After 48 hours, take out the sample and weigh it, and calculate the corrosion rate. The results are shown in Table 3.
[0071] Table 3
[0072] <![CDATA[Corrosion rate (g / (m 2 ·h))]]> <![CDATA[Corrosion rate (g / (m 2 ·h))]]> Example 1 0.326 Comparative Example 1 0.588 Example 2 0.299 Comparative Example 2 0.972 Example 3 0.309 Comparative Example 3 0.384 Comparative Example 4 0.453
[0073] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 and 3 in Table 3, it can be found that the adhesive for composite glass fiber cloth copper clad laminate prepared by the present invention has good corrosion resistance.
[0074] By comparison, the corrosion rates of Examples 1 to 3 are lower than that of Comparative Example 1, indicating that the surface of the modified graphene oxide modified by hexadecyltrimethoxysilane has a long alkyl chain, which makes it hydrophobic and improves the corrosion resistance; the corrosion rates of Examples 1 to 3 are lower than that of Comparative Example 2, indicating that the amine groups on the surface of the graphene oxide after amination have a strong adsorption effect on metal cations, so that zinc ions and aluminum ions are tightly adsorbed on the surface of the graphene oxide, which is beneficial to the formation of a layered double metal hydroxide layer, improves the dispersibility of graphene oxide, and helps the layered structure of graphene oxide to be dispersed in the adhesive to form a maze effect, prolongs the diffusion path of oxygen and water molecules to the metal surface, and improves the corrosion resistance of the adhesive.
[0075] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. An adhesive for composite glass fiber cloth copper clad laminate, characterized in that: Calculated by weight, it mainly includes 8-12 parts of modified graphene oxide, 90-110 parts of epoxy resin, 55-65 parts of flame retardant curing agent, and 15-25 parts of γ-aminopropyltrimethoxysilane; The modified graphene oxide is prepared by aminated graphene oxide, metal hydroxide deposition, and hexadecyltrimethoxysilane modification; The flame retardant curing agent is prepared by hydrolyzing DOPO-based trimethoxysilane, gamma-aminopropyl dimethoxymethylsilane and dimethyl dimethoxysilane.
2. A method for preparing an adhesive for glass fiber cloth copper clad laminate composite, characterized in that: The method comprises the following preparation steps: (1) Mix aminated graphene oxide and deionized water in a mass ratio of 1: (400-600) and ultrasonicate for 2-3 h to obtain a suspension; mix zinc nitrate hexahydrate, aluminum nitrate nonahydrate, urea, and deionized water in a mass ratio of (2-2.2): (1-1.2): (8.5-8.7): (25-35) and drip into the suspension at a rate of 3-5 g / min. Stop dripping when the pH value is 8.5-9.0 and stir at a speed of 60-80 r / min at room temperature. Stir for 0.5-1.5h, wash the solid product with deionized water and centrifuge until the pH value of the washing solution is 7.0, freeze-dry the solid product for 22-26h, immerse in a 10% volume concentration of hexadecyltrimethoxysilane ethanol solution, ultrasonicate for 25-35min, stir at 200-300r / min at room temperature for 0.5-1.5h, filter, wash the filter residue with deionized water for 3-5 times, freeze-dry for 22-26h, and obtain modified graphene oxide; (2) γ-aminopropyldimethoxymethylsilane, DOPO-trimethoxysilane and dimethyldimethoxysilane were mixed in a molar ratio of 1:1:1, methyl ethyl ketone (2-4 times the mass of DOPO-trimethoxysilane) and anhydrous methanol (1-3 times the mass of DOPO-trimethoxysilane) were added, and 1 mol / L sodium hydroxide solution (0.02-0.04 times the mass of DOPO-trimethoxysilane) was added dropwise at 20-30 drops / min at 0°C. The reaction was continued at 0°C for 0.5-1.5 h, and the temperature was raised to 70-80°C and the reaction was continued for 25-35 h. Dichloromethane (equal volume of methyl ethyl ketone) and deionized water (equal volume of methyl ethyl ketone) were added and stirred, and the mixture was allowed to stand for stratification. The organic phase was taken and the operation was repeated 3-5 times. The organic phase was dried under reduced pressure at 40-45°C and 40-60 kPa for 4-6 h to obtain a flame retardant curing agent. (3) The modified graphene oxide and epoxy resin are stirred at a mass ratio of 1:(9-11) at 170-190°C at a rate of 60-80 r / min for 0.5-1.5 h, and a flame retardant curing agent (0.5-0.7 times the mass of the epoxy resin) and γ-aminopropyltrimethoxysilane (0.1-0.3 times the mass of the epoxy resin) are added. The stirring is continued for 10-20 min, and vacuum degassing is performed for 10-20 min to obtain an adhesive for glass fiber cloth copper clad laminate composite.
3. The method for preparing a glass fiber cloth copper clad laminate adhesive according to claim 2, characterized in that: The graphene oxide in step (1) is industrial-grade graphene oxide; the aminated graphene oxide is prepared by mixing graphene oxide and deionized water in a mass ratio of 1:(190-210), ultrasonicating for 25-35 min to obtain a graphene oxide suspension, mixing the graphene oxide suspension and ethylenediamine in a mass ratio of 1:(7-8), stirring at 65-75° C. and a speed of 60-80 r / min for 1.5-2.5 h, centrifuging to obtain a solid product, washing it with deionized water for 3-5 times, and freeze-drying it for 46-50 h.
4. The method for preparing a glass fiber cloth copper clad laminate adhesive according to claim 2, characterized in that: The DOPO-based trimethoxysilane in step (2) is prepared by mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and dimethoxymethylvinylsilane in a molar ratio of 1:1, adding chloroform in an amount of 0.7 to 0.9 times the mass of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, stirring at 60 to 80 r / min for 3.5 to 4.5 h at 65 to 75 ° C, adding azobisisobutyronitrile in an amount of 0.01 to 0.03 times the molar number of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to the above system in three times, stirring at 65 to 75 ° C at a rate of 60 to 80 r / min for 9 to 11 h, cooling to room temperature, and rotary evaporating at 35 to 45 ° C for 2 to 3 h.
5. The method for preparing a glass fiber cloth copper clad laminate adhesive according to claim 2, characterized in that: The epoxy resin in step (3) is E-51 epoxy resin.
